Physical, Verbal, Relational and Cyber (PVRC) Bullying and High Academically Oriented Students - Urazova, Ainura (Nazarbayev University Graduate School of Education, 2020)
The aim of the current study was to identify the prevailing type of bullying among academically talented secondary students. Even though the problem of school bullying is not new, it continues to arouse interest from different parties involved in educational process due to its complex nature. It is crucial to investigate the phenomenon of school bullying among gifted and talented students as little research has been conducted specifically on academically talented students and bullying. The study focused on four types of bullying: physical, verbal, relational and cyber. Furthermore, the study investigated the differences in physical, verbal, relational and cyber bullying perpetration and victimization across participants’ gender, self-reported academic achievement, ethnical background and residence (students live either in dormitory or in an urban area with their families). The study used a non-experimental explanatory cross-sectional research design. The research site was one private secondary school in Kazakhstan which serves academically talented youth. Due to the sensitive nature of the topic, the study recruited only those participants, who already reached the age of 18, using non-probability purposive sampling. The current study collected data using an online survey which was based on the research instrument employed in the study of bullying conducted by Stubbs-Richardson, Sinclair, Goldberg, Ellithorpe and Amadi (2018). Frequency distributions, a cross-tabulation with a chi-square have been used to analyse gathered data. The study found that the rate of both bullying perpetration and victimization was considerably low, with verbal bullying being comparatively higher and cyber bullying being the lowest.
Keywords: physical, verbal, relational, cyber bullying, academically talented students